Corporate environmental protection under uncertainty - Iulie Aslaksen; Terje Synnestvedt (Statistics Norway, Research Department, 2003)
Investment in pollution prevention technologies are often made under significant uncertainty about the future pay-off from the investments. However, as time passes some of the uncertainties may be resolved by new information, implying that the timing of investments becomes an important issue for the company. This paper focuses on uncertainty about a future environmental tax, and shows, within a two period model, that a specific tax uncertainty, standing alone, does not create any incentives for early investments. However, introducing a market share increase linked to the investment, the tax uncertainty may strengthen the incentives for early investments.
Keywords: D81; H25; Q20; 330; Uncertainty; Irreversibility; Environmental management; Tax uncertainty; Option value